Chrysophanol Relieves Cisplatin-Induced Nephrotoxicity via Concomitant Inhibition of Oxidative Stress, Apoptosis, and Inflammation - Ma, Siqing; Xu, Heng; Huang, Weihua; Gao, Yongchao; Zhou, Honghao; Li, Xiong; Zhang, Wei (Frontiers in Physiology, 2021)
Cisplatin (CDDP) is one of the most frequently prescribed chemotherapy medications. However, its nephrotoxicity which often leads to acute kidney injury (AKI), greatly limits its clinical application. Chrysophanol (CHR), a mainly active anthraquinone ingredient, possesses various biological and pharmacological activities. In this study, we aimed to investigate the underlying protective mechanisms of CHR against CDDP-induced AKI (CDDP-AKI) using C57BL/6 mouse and human proximal tubule epithelial cells. In vivo, we found that pre-treatment with CHR greatly relieved CDDP-AKI and improved the kidney function and morphology. The mechanistic studies indicated that it might alleviate CDDP-AKI by inhibiting oxidative stress, apoptosis, and IKKβ/IκBα/p65/transcription factor nuclear kappa B (NF-κB) inflammation signaling pathway induced by CDDP. Moreover, we found that the cell viability of HK2 cells reduced by CDDP was partially rescued by CHR pre-incubation. Flow cytometry results further indicated that CHR pre-incubation suppressed CDDP induced cellular reactive oxygen species (ROS) generation and inhibited cell apoptosis in a dose-dependent manner. In summary, our results suggested that CHR might be a novel therapy for CDDP-induced AKI.